OPERATIONAL ALGORITHMS FOR TESTING FIRE-TECHNICAL EQUIPMENT - Sergey M. Dymov; Maxim V. Vishchekin; Aleksandr M. Aleksandrov; Maxim I. Dorozkin (Aktualʹnye voprosy požarnoj bezopasnosti, 2024)
The article deals with the issues of the scope and sequence of fire-technical equipment tests. There is shown the difference in tests within product commissioning and during tests confirming the daily performance of products. There is considered the question about the need to develop GOST-type standards on the topic of product testing in conditions close to real operation.